Annals of tropical medicine & parasitology (Biomedical Reference Collection: Comprehensive., 2011)
"Liverpool School of Tropical Medicine. Scientific record; compiled by Dorothy Allmand" (a history of the school and of its activities): v. 15, 1921, p. [1]-47.